Thermodynamic analysis of decarbonizing NGCC power plants by the tail-end green ammonia-driven calcium looping - He, Song; Zeng, Xuelan; Zheng, Yawen; Zhu, Mingming; Wang, Dan; Wang, Junyao (Elsevier, 2025)
This work proposes a novel ammonia driven tail-end calcium looping (CaL) process to capture carbon emission from natural gas combined cycle (NGCC) power plants for net-zero energy. Two integration schemes are introduced, including sensible heat thermochemical recuperation (SHTR) and carbonation heat thermochemical recuperation (CHTR) driven by combustion of partially cracked ammonia as a zero-carbon fuel. Results show that energy penalties can be reduced from 9.6 % in the NGCC power plant with the CaL-Oxy method to 1.8 % in the SHTR scheme and 1.4 % in the CHTR scheme, respectively. Comparing with the NGCC base power plant and the NH3-based thermochemical recuperation power plant, energy savings can be achieved at 5.44 MJLHV/kg CO2 in the SHTR scheme and 6.73 MJLHV/kg CO2 in the CHTR scheme. Additionally, exergy analysis shows that the reduction of exergy destruction in the carbonation and calcination processes determines the thermodynamic performance enhancement. Cascaded heat recovery of carbonation heat and the heating supply method of calcination narrow the energy level difference, contributing to the reduction of exergy destruction. Sensitivity analysis indicates that reorganizing a more efficient thermodynamic cycle can offset the energy consumption of CO2 capture from flue gas, resulting in an optimized negative energy penalty at −0.8 %.
Keywords: 4004 Chemical Engineering; 40 Engineering; 13 Climate Action; Energy; 4008 Electrical engineering; 4012 Fluid mechanics and thermal engineering; 4017 Mechanical engineering; Calcium looping; Ammonia; Thermochemical recuperation; Post-combustion CO2 capture